THE ROLE OF CONSUMER TRUST MEDIATES THE INFLUENCE OF LIVE STREAMING ON PURCHASING DECISIONS FOR N’PURE PRODUCTS ON TIKTOK SHOP - Nilna Muna; Ni Luh Putu Sulistya Dewi (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to identify the role of consumer trust in mediating the influence of live streaming on the purchase decision of N’pure products on TikTok shop.Design/Methodology/Approach – The sample in this study consisted of 108 respondents, with the sample selection conducted through purposive sampling. Data were collected using a questionnaire distributed online via Google Form and analyzed with descriptive statistical analysis to describe the collected data and inferential statistical analysis using the Partial Least Square-based Structural Equation Modeling method with SmartPLS 4.1.Findings – The research results show that 1) Live streaming does not have a significant effect on Purchase Decisions, 2) Live streaming has a positive and significant effect on consumer trust, 3) Consumer trust has a positive and significant effect on Purchase Decisions, and 4) Consumer trust has a positive and significant effect in mediating Live Streaming on Purchase Decisions.Conclusion and Implications – These findings emphasize the importance of trust, which can be enhanced through host credibility, visual marketing strategies, and clear and easily understandable product information. The implication of this research is that N’pure needs to improve the quality of live streaming, especially in building consumer trust to encourage higher purchase decisions. Keywords: Consumer Trust, Live Streaming, Purchasing Decisions